2016
DOI: 10.1016/j.jenvman.2016.02.030
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lameness on the environmental performance of milk production by rotational grazing

Abstract: Dairy production leads to significant environmental impacts and increased production will only be feasible if the environmental performance at farm level permits a sustainable milk supply. Lameness is believed to become more prevalent and severe as herd sizes increase, and can significantly reduce milk output per cow while not influencing other attributes of the production system. The objective of this work was to quantify the effect of lameness on the environmental performance of a typical grazed grass dairy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…The development of these tools is need driven design. In all, DTs can fit within the entire value chain of livestock systems (Chen, White & Holden, 2016;Singh et al, 2016;Waters-Bayer, 2016). In the production stages, DTs are already playing key roles in livestock monitoring, health and diseases diagnosis as well as communication (social networking) with extension workers (ibid).…”
Section: Can Dts Fit In the Livestock Systems How And Where?mentioning
confidence: 99%
“…The development of these tools is need driven design. In all, DTs can fit within the entire value chain of livestock systems (Chen, White & Holden, 2016;Singh et al, 2016;Waters-Bayer, 2016). In the production stages, DTs are already playing key roles in livestock monitoring, health and diseases diagnosis as well as communication (social networking) with extension workers (ibid).…”
Section: Can Dts Fit In the Livestock Systems How And Where?mentioning
confidence: 99%
“…Lameness has been identified as the third most important health-related economic loss, after fertility and mastitis (Bruijnis et al, 2010;Alawneh et al, 2011;Huxley, 2013). Lameness also has serious negative consequences on animal welfare (Leach et al, 2012;Navarro et al, 2013) and the environment; for example, increased greenhouse gas emissions (Mostert et al, 2018), acidification, eutrophication, and fossil fuel depletion (Chen et al, 2016). Lameness has the potential to reduce the overall lifetime performance of dairy cows due to milk production loss and culling (Huxley, 2013), as well as having the potential to further affect sustainability by increasing the total greenhouse gas emissions per unit of milk produced (Mostert et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Lameness is one of the major problems associated with dairy production, affecting all three pillars of sustainability. Lameness is associated with negative animal welfare impacts (Rushen, 2001, O'Callaghan, 2002, Mee and Boyle, 2020, substantial economic losses (Bruijnis et al, 2010), and environmental consequences, including increased emissions of greenhouse gases (Mostert et al, 2018), acidifying gases or eutrophying substances (Chen et al, 2016). Focusing on economics, Bruijnis et al (2010) reported that lameness is amongst the most important health related economic losses after mastitis.…”
Section: Introductionmentioning
confidence: 99%
“…Lameness is the third most important disease related economic loss, after both fertility and mastitis (Bruijnis et al, 2010), whereby lameness has been shown to have negative associations with various aspects of both production and reproduction (Bicalho et al, 2008;Alawneh et al, 2011; In prep. With compromised production effects associated with lameness, it is not surprising that recent findings have also reported on the negative environmental consequences, such as increased greenhouse gas emissions (Mostert et al, 2018), acidification, eutrophication and fossil fuel depletion (Chen et al, 2016). As well as this, the welfare of lame cows is also at risk due to the pain and behavioral changes associated with this debilitating disease (O'Callaghan, 2002;Navarro et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation